Funding Local Authorities to support former Independent Living Fund (ILF) recipients : The Former ILF Recipient Grant. Technical Consultation: Government Response.: The Former ILF Recipient Grant. Technical Consultation: Government Response. (May 2016) - Great Britain., Department for Communities; Local Government,
No abstract available